Targeted inhibition of gastric cancer progression via a chitosan-RNU11 siRNA nanoparticle delivery system: mechanistic insights and therapeutic potential - Peng Cheng; Zhengrong Zhong; Yanling Wang; Caituan Feng; Jitong Zheng; SuogaoWang; Xiangjun Meng; Dong Wang (Cancer Nanotechnology)
Abstract Background Gastric cancer (GC) remains a leading cause of cancer-related mortality worldwide. The prognosis for advanced GC is poor, necessitating innovative therapeutic strategies. Small interfering RNA (siRNA) offers a promising avenue for gene-specific cancer treatment. However, effective delivery of siRNA remains a challenge. Chitosan, a natural biopolymer, has demonstrated potential as a nanocarrier due to its biocompatibility and ability to facilitate targeted delivery. This study investigates the therapeutic efficacy of a novel chitosan-RNU11 siRNA drug delivery system in inhibiting GC progression and elucidates its underlying mechanisms. Methods Chitosan nanoparticles (CH-NP) loaded with RNU11 siRNA (Si-RNU11 + CH-NP) were synthesized and characterized for size, zeta potential, and siRNA release efficiency. GC cell lines (AGS and HGC27) were treated with various formulations, and functional assays, including EdU proliferation, Transwell invasion/migration, and cell cycle/apoptosis analysis, were conducted. The in vivo efficacy of Si-RNU11 + CH-NP was evaluated in GC xenograft mouse models. Expression of Wnt pathway components was analyzed by Western blot and qRT-PCR. Results Si-RNU11 + CH-NP exhibited a uniform size distribution (~ 85 μm) with a zeta potential of + 14 mV, ensuring colloidal stability and efficient cellular uptake. siRNA release exceeded 95% under physiological conditions. In vitro, Si-RNU11 + CH-NP significantly reduced GC cell proliferation, migration, and invasion while inducing apoptosis and G1/G2 cell cycle arrest. Western blotting revealed downregulation of Wnt pathway components, including Wnt1, β-catenin, GSK-3β, c-myc, and CyclinD1. In vivo, Si-RNU11 + CH-NP treatment led to a significant reduction in tumor size and decreased expression of Ki67 and RNU11. Conclusion This study demonstrates that the chitosan-RNU11 siRNA drug delivery system effectively inhibits GC progression by targeting the Wnt signaling pathway. The integration of chitosan nanoparticles and RNU11 siRNA provides a novel therapeutic approach for GC, addressing the critical challenge of efficient siRNA delivery and highlighting the potential for clinical application.